Avaliaç\~ao do Programa Nacional de Apoio à Captaç\~ao de Água de Chuva e Outras Tecnologias Sociais (Programa Cisternas), à luz dos objetivos de Desenvolvimento Sustentável - César Nunes De Castro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– In 2012, as a result of the Rio+20 Conference of the United Nations (UN), the Sustainable Development Goals (SDGs) were created, including access to drinking water and basic sanitation (challenge 6 of the SDGs). In Brazil, the semiarid region is the region where achieving the goals of SDG 6 is most challenging. Throughout the 1980s and 1990s, a new proposal to deal with the issue of water scarcity and droughts, regular event in that region,began to take shape under the aegis of the idea of coexistence with the semiarid region. Some innovative approaches emerge from this perspective, including the use of cisterns for the storage of rainwater by the rural population. The purpose of this article is to analyze this initiative since its inception (before being incorporated into the list of public policies of the federal government) until the present day, in light of its impacts on the benefited region and its contribution to SDG 6. Evidence presented in this article indicates that the Cisterns Program's contribution to achieving the goals of SDG 6 is significant. Due to the evidence recorded in this, and in many other articles, of the positive impacts of cisterns on beneficiaries, the continuation of the Cisterns Program is justified, with the purpose of one day to mitigating the most harmful effects of droughts on the population of the Brazilian semiarid region, thirst and hunger.
Keywords: Q25; Q28; 330; Sustainable Development Goals; semiarid; cisterns program